Housing market cycles and duration dependence in the United States and Canada - Rose Cunningham; Ilan Kolet (Bank of Canada, 2007)
Housing wealth is a large component of total wealth and plays an important role in aggregate business cycles. In this paper, we explore data on real house price cycles at the aggregate level and city level for the United States and Canada. Using a panel of 137 cities, we examine the duration, size, and correlations of housing market cycles in North America. We find that North American housing cycles are long, averaging five years of expansion and four years of contraction, and there is a fairly high degree of correlation in house price cycles between U.S. and Canadian cities. We estimate a discrete time survival model with a probit specification for house price expansions and contractions. This model allows us to test for duration dependence. We find that housing market expansions have positive duration dependence since their exit probabilities increase with duration, while contractions seem to have no duration dependence. Standard determinants of house prices (interest rates, income and population growth) are included as controls.
Keywords: E32; R21; C41; 330; Business fluctuations and cycles; Econometric and statistical methods; Städtischer Immobilienmarkt; Immobilienpreis; Konjunktur; Dauer; Ökonometrisches Modell; USA; Kanada